Software educativo en la disciplina de computación para mejorar el proceso de enseñanza –aprendizaje de los niños y niñas del séptimo año básica de la escuela fiscal mixta Juan Benigno Vela, cantón Echeandía, provincia de Bolívar; en el periodo lectivo 2011- 2012 - Allaica Yanchaliquin, María Doraliza (2012)
The present investigation, it is directed to the design of an educational software in the calculation discipline to improve the teaching process - the children's learning and girls of the basic seventh year of the mixed fiscal school Juan Benign Candle, Echeandía, County of Bolívar; in the period lectivo 2011-2012, I work that has been carried out being based on a responsible and precise investigation in order to determine all the necessary aspects to base the proposal. In the first chapter we make reference to the theoretical mark of the investigation, where it is presented topics related with the software, characteristic, classification, their pedagogic use, the multimedia is mentioned, the components, characteristic, elements. In the legal mark, we speak of regulations and laws that make reference to the modernization of the educational system, to like it should be inclined to use the technology in the pedagogic process. In the Theory referencial we expose the history of the school, their mission and vision. In the chapter II, reference is made to the methodological strategies that were used for the rising of the information and the prosecution of the results. In the chapter III that it corresponds to the analysis of the results, expose the tabulation of the surveys with their respective analysis, so much of those carried out to the educational ones as of those carried out the students, it is made the analysis and the confirmation of the hypothesis, you think about in a clear form the conclusions and recommendations of the carried out investigation. In the chapter IV the proposal is presented that we have denominated it design of an educational software in the calculation discipline to improve the teaching process - the children's learning and girls of the basic seventh year of the mixed fiscal school Benign Juan, where they think about the IX objectives that we aspire to reach with the application of the proposal, step it is described to step its realization and the results reached with the application